PENGARUH MANAJEMEN KELAS TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA KRISTEN - Ranafika Br Sembiring (Sekolah Tinggi Teologi Duta Panisal, 2020)
In the world of education especially in schools, management class is one of the needs for the ongoing process of teaching and learning activities between teachers and students. With good and regular management in the classroom, automatically students' interest willincrease in learning and specifically in Christian Religious Education. The role of the teacher as a manager in the class is not easy but it is very successful. So in this study, the authors prove that class management supports student interest in learning or not. If you donot agree to eat, the writer will give steps to manage the class of students' conversations about learning interest, and if approval, the writer will give steps to increase student learning interest. The research method used is a quantitative research method with a oneshot case study pre-experiment. Through observation and questionnaires (questionnaire distribution). The study was conducted in grades 4, 5 and 6 in the Christian religion class at Tiga Rukun Harapan Jember Elementary School. The results of research conducted by the author prove that good management classes affect student learning of Christian Religious Education subjects.